ANALISIS YURIDIS PENGUASAAN TANAH MASYARAKAT HUKUM ADAT KECAMATAN SIMANGAMBAT PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 35 / PPU-X/ 2012 - AHCMAD SANDRY NASUTION (PREMISE LAW JURNAL, 2015)
The regulations on the system of land tenure practiced by indigenous people in the Regulation of Legislation showed that the recognition of the existence of indigenous people with regard to the aspects of land, forestry, plantation, and living environment has been very strong and it has been proven that such arrangement has been stated in the Regulation of Legislation, although, up to now, there is no harmonious legal instrument andadequate implementation yet. The position of law (legal position) over the system of land tenure practiced by indigenous people in Simangambat Subdistrict is factually still recognized by the community. Where the adat land of Simangambat Subdistrict called “Tanah Adat Luhat Simangambat” exists is currently still recognized, but juridically, the existence of the adat land has not been able to be implemented because Local Regulation for that purpose has not been issued yet. According to the Decision of Constitutional Court on adat forest, Adat Forest is the forest belongs to the local indigenous people and it can be used as a guideline in the issuance of Local Regulation. The legal action taken was by advocating the community to socialize the Decision of Constitutional Court No 35/ PUU-X/ 2012 and provide recommendations to the government to issue a Local Regulation. Keywords: Land Tenure, Indegenous People, State Land, Adat Forest.